Impact of US-China Trade War on the Network Topology Structure of Chinese Stock Market - Yao, Hongxing; Lu, Yanyu; Memon, Bilal Ahmed (Journal of Asian Business Strategy, 2019)
Sustainable environment is needed for a progressive stock market. Simultaneously, international events of crisis exert chaos among investors and affect progress of the stock market. It is observed that a mature stock market can resist external crisis effectively. On March 23 2018, a trade war broke out between China and the United States. As a representative of emerging economies, how will the network structure of China’s stock market change when China and the United States fueled a trade war? We use Pearson’s coefficient to construct the correlation between stocks, and set up a network for the Chinese stock market in three periods (before trade war, during trade war, and the overall period) through the threshold network for analysis. We find that recent trade war between China and US changes the topological structure of China’s stock market network, making it denser and more likely heading towards a crisis. At the same time, we find that after 30 years of development, China’s stock market has become more mature and its ability to resist external risks has improved. This study will be of a great significance for the government to regulate the stock market and for others to study the stock market of an emerging economy.